(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Effective inventory management is a cornerstone of pharmaceutical operations, ensuring timely availability of medications, minimizing waste, and maintaining cost efficiency. Smart inventory systems powered by automation, artificial intelligence (AI), and data analytics are transforming the traditional role of pharmacy technicians. This paper explores how automation supports technicians in managing pharmaceutical inventories, highlights current technologies in use, and evaluates their impact on workflow efficiency, accuracy, and patient safety.